ERROR ANALYSIS ON DETERMINATION OF SPECIFIC HEAT OF AGRICULTURAL PRODUCTS USING MIXTURE METHOD - Ropiudin .; Budi I. Setiawan; Radite P.A. Setiawan (Jurnal Keteknikan Pertanian, 2006)
ABSTRACT This paper reporting method of error analysis in determination of specific heat of agricultural product using mixture method. There are six Variables evaluated on error measurement, those are: mass of water, mass of simple, equilibrium temparature, water temparature, sample temparature and calorimeter temperature. As the results of experiment on potatoes and carrot, calorimeter temperature gave biggest error contribution based on simulation conducted using Visual Basic Application (VBA) at Microsoft Word. Keyword: error analysis, Specific heat, VBA